Aortic root replacement in severe left ventricular dysfunction: The added value of beating‐heart surgery. Issue 11 (1st September 2022) - Ganizada, Berta; Heuts, Samuel; Willems, Colin; Cortenraad, Inez; Tunnissen, Willemijn; Maessen, Jos G.; Bidar, Elham; Natour, Ehsan
Abstract: There are limits to the use of cardioplegic arrest during complex cardiac surgical procedures, especially in patients with severe left ventricular dysfunction. In the current report, we graphically present the detailed surgical strategy and technique for beating‐heart aortic root replacement with concomitant coronary bypass grafting, for patients otherwise deemed inoperable. With support of cardiopulmonary bypass (CPB), beating‐heart bypass surgery is realized, after which the bypass grafts can selectively be connected to the CPB, preserving coronary flow. Then, on the beating and perfused heart, a complex procedure such as aortic root replacement can be performed, without jeopardizing postoperative cardiac function. However, several important caveats and remarks regarding the use of beating‐heart surgery should be considered, including: coronary perfusion verification and maintenance, temperature management, and prevention of air embolisms. By use of this strategy, risks associated with cardioplegic arrest are minimized, while it circumvents the potential need for long‐term postoperative extracorporeal membrane oxygenation.